Selective Sampling of Species and Fossils Influences Age Estimates Under the Fossilized Birth–Death Model - Matschiner, Michael (Frontiers in Genetics, 2019)
The fossilized birth-death (FBD) model allows the estimation of species divergence times from molecular and fossil information in a coherent framework of diversification and fossil sampling. Some assumptions of the FBD model, however, are difficult to meet in phylogenetic analyses of highly diverse groups. Here, I assess the impact of extreme model violations, including diversified sampling of species and the exclusive use of oldest fossils per clade, on divergence times estimated with the FBD model. Based on simulated datasets, my results demonstrate that these model violations can produce dramatically overestimated divergence times when the FBD model is used for inference. In contrast, divergence times estimated with CladeAge, a method that uses information about the oldest fossils per clade together with estimates of sampling and diversification rates, are accurate under these conditions. Practitioners of Bayesian divergence-time estimation should therefore ensure that the dataset conforms to the expectations of the FBD model or estimates of sampling and diversification rates should be obtained a priori so that CladeAge can be used for the inference.